Micro-Characterization of Indoor Deposited Particles Using FTIR, SEM-EDS, and XRD Techniques: A Case Study of a University Campus, Bangladesh - Mamun Mahmud; Kazi ABM Mohiuddin (Aerosol and Air Quality Research)
Abstract Micro-characterization of indoor atmospheric particles is essential for understanding atmospheric particle consequences on human health. In this study, the atmospheric particles were collected from inside the different buildings of KUET campus. The samples underwent characterization through FTIR, SEM-EDS, and XRD techniques. Among the four sampled locations, the New Academic Building (NAB) had the highest rate of atmospheric particle deposition at 3.96 µg cm−2 day−1. The FTIR analysis indicated that the primary functional groups present across all samples were organic, specifically hydroxyl (-OH), aliphatic carbon (-CH2), carbonyl (-CO), and amino (-NH2) groups. The morphological analysis by SEM depicted the shape of indoor particles as angular, micro-flake, cubic, and irregular with the major chemical compositions of C, O, Al, Si, Ca, Na, Fe, and Mg of which Si and Fe were dominant in CEC and CEL sites which most likely originated from construction activities and dust from paved and unpaved roads. The average crystallinity of studied atmospheric particles was found to be a minimum of 27.3% at RH and a maximum of 64.5% at NAB sites and the corresponding crystalline size was 11.10 nm and 42.92 nm respectively. Quartz mineral in the inorganic fraction of atmospheric particles was found predominantly in every sample which most likely originates from soil erosion, construction activities and vehicular emissions. The outcome of this study will enhance our understanding of organic and inorganic compounds in atmospheric particles and their significance regarding radiative forcing, health impacts, and policy considerations for atmospheric particle sources.